#TITLE_ALTERNATIVE# - RUSTAMIAJI (NIM 10503053), TOMI
Voltammetric measurements of heavy metal ions with mercury electrode has good sensitivity and selectivity, despite problems of its toxicity. Modification of mercury electrode into copper amalgam electrode has the benefit of minimum use of mercury and less toxicity. The other advantage of copper amalgam electrode is its higher overpotential for hydrogen and its wider potential window in the negative potential value. Square Wave Stripping Voltammetry technique provides a better alternative for trace heavy metal analysis using copper amalgam electrode, because it can produce larger signal due to preconcentration of analytes on the electrode surface. From the experiment it is found that optimum pH for measurement of Pb2+ and Zn2+ is 4,5 and optimum pH for Cd2+ is 6. The linear range of the calibration curve of each ion is different. To determine the sensitivity and selectivity of the copper amalgam electrode, calibration curves was made in the concentration range of 0,1 ppm to 10 ppm. From the calibration curves, it is found that detection limit for Pb2+, Cd2+, and Zn2+ ions are 50,7 ppb, 43,9 ppb, and 519 ppb; respectively. Accuracy of the analysis is good with percent recovery ranging from 91% to 103%.